Senam SKJ 2004 SENAM SKJ 2004 TRAINING CAN IMPROVE PHYSICAL FITNESS - I Putu Astrawan; I Putu Prisa Jaya (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2022)
Physical training is useful so that the body does not quickly experience excessive fatigue during strenuous physical activity, prevents degenerative diseases and improves health status. Physical training has an important role to maintain and improve the degree of physical fitness during this COVID-19 pandemic. This study aims to determine the Senam 2004 SKJ gymnastics training can improve physical fitness. This type of research is experimental with the randomized pretest posttest control group design. The sample of this study was 20 students of the Physiotherapy Study Program divided into 2 groups. Group 1 was given SKJ 2004 gymnastics training and Group 2 as a control group, with a frequency of exercise 3 times a week for 6 weeks. The component of physical fitness in this case is VO2Max measured by the Bleeps Test (MFT) instrument. The results of the study on age, height, weight and BMI were analyzed descriptively in both groups. Test the normality of the data using the Shapiro-Wilk Test and test the homogeneity of the data using the Levene Test. Intra-group differences in the mean of VO2Max were tested by paired t-test. The results of the different test with t-paired before and after training, the results obtained in Group 1 and Group 2 were significantly different (p <0.05). The results of the VO2Max test between the two groups before and after the training were tested using the t-independent sample test. The average VO2Max in both groups before training with p value = 0.27 (p>0.05) and after training with p value = 0.00 (p<0.05). In Group 1, the average VO2Max (L/m) before training was 26.45 and the average after training was 38.54 with a difference of 12.09 and a percentage increase of 45.70%. Meanwhile in Group 2, the average VO2Max before training was 25.51 and the average after training was 27.52 with a difference of 2.06 and the percentage increase was 8.07%. This shows that the treatment of group 1 and group 2 both gave a change effect. However, the improvement in group 1 was better than group 2. It was concluded that SKJ gymnastics training can improve physical fitness.